Pengaruh Media Pembelajaran Video Tiktok Materi Interaksi Desa Kota Terhadap Hasil Belajar Geografi Pada Siswa SMAN 9 Pontianak - Sulistyaningrum, Fitri; Maria, Haratua Tiur; Karolina , Venny (LP. Ma'arif Janggan Magetan, 2023)
This research aims to determine the effect of learning media using TikTok videos with village-city interaction material on geography learning outcomes for students at SMAN 9 Pontianak. The method used in this research is the experimental method. The form of experiment used was One-Group Pretest-Posttest and a class XII sample of 20 students. Data analyzed using pretest and posttest are presented in bar charts and data management uses SPSS. The results of the Paired Samples Statistics Test show that the average for the pretest is 46.75 and the posttest is 87.80, so there is a fairly large increase between the average value of the pretest and posttest. The results of the Paired Samples Test show a significance value of 0.000, which is smaller than 0.005. So it can be concluded that there is a significant influence between the TikTok video learning media, village-city interaction material on geography learning outcomes for students at SMAN 9 Pontianak.